The Implementation of Internet Website Strategy Of Guidance And Counseling At University In Industrial 4.0 Content - Suwandi Suwandi (IAIN Salatiga, 2022)
Guidance and counseling are the process of providing assistance to individuals or groups of individuals at every age stage so that the supervisor can understand and direct himself in accordance with the norms and norms that exist in society so that the individual feels happy and effective in his behaviour and builds his welfare. Guidance is a process that provides assistance to individuals or groups of individuals at every age stage. This study was carried out with the goals of developing web-based social media advice, implementing guidance web pages, overcoming obstacles that have been encountered, and developing students' potential. The ADDIE development research technique was used for this study's data analysis, followed by an assessment of the obtained findings. There are 80 students enrolled at a university in North Sumatra, and 12 of those students have contributed to academic mentoring at the institution. Based on the number of students who utilize the internet as a tutoring service, there are 12 students who have contributed. According to the findings of internet-based online media about university assistance, the study sample consists of eighty different students.Key Words: Social Media, Developing ADDIE